Peningkatan Pemahaman Konsep Tentang Bagian Tumbuhan melalui Media Audio Visual pada Siswa Kelas IV SD Negeri 3 Menawan - Ayu Alfiani (Universitas Sebelas Maret, 2020)
Lack of students' understanding of a learning concept can be related to the choice of media in learning activities. The use of audio-visual media can display real objects as well as parts that are difficult to present directly in a short time and played repeatedly to improve students' understanding of learning concepts in large and small groups. This type of research is Classroom Action Research (PTK). The stages carried out in this study include planning, implementing actions and observations, as well as reflection which are carried out in two cycles. This research was conducted on fourth grade students of SD Negeri 3 Menawan, Klambu district, Grobogan district. The results of the study were indicated by the percentage of student learning outcomes that had increased by 13%. In the first cycle it was 67%, while in the second cycle it became 80% and there was an increase in the average score of students from 70 to 75. This shows that the use of audio-visual media can improve understanding of the concept of plant parts, especially in grade IV SDN 3 Menawan.